1984
DOI: 10.1007/bf00202979
|View full text |Cite
|
Sign up to set email alerts
|

Todeszeitbestimmung durch Messung der zentralen Hirntemperatur

Abstract: The central brain temperature was recorded in 53 human corpses, stored at constant ambient temperatures between 10 degrees and 30 degrees C. The measurements were started on average 1.6 h post mortem and continued for 8-50 h. The sigmoidal shape of the temperature curves fitted the mathematical model of Marshall and Hoare (1962). This model provides a precise description of the temperature curves. For 44 corpses, studied at temperatures between 10 degrees and 25 degrees C, the time of death was calculated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
5
0
4
Order By: Relevance
“…Usually clothing decreases the evaporation and conduction, but the data on the effect of wet clothing is limited. To our known the effect of wet clothing on body cooling has only been studied by Henssge and Brinkmann [14] in association of a court case. In that study, 12 clothed cadavers were immersed for 4-10 min in water and were left overnight with wet clothing in closed room or were laid out on wet lawn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually clothing decreases the evaporation and conduction, but the data on the effect of wet clothing is limited. To our known the effect of wet clothing on body cooling has only been studied by Henssge and Brinkmann [14] in association of a court case. In that study, 12 clothed cadavers were immersed for 4-10 min in water and were left overnight with wet clothing in closed room or were laid out on wet lawn.…”
Section: Discussionmentioning
confidence: 99%
“…The most important drawback is the current limited supply of case-derived data to be applied on choosing correction factors [8,13]. The knowledge about the effect of water immersion on body cooling is based on a the study by Henssge and co-worker [12,14], in which on 29 corpses with known time of death were immersed undressed in a tub holding 1,000 l water of temperatures 20, 10 or 0 8C. It was found that the wet naked bodies cooled more rapidly than bodies in standard environment and that the body weight had to be multiplied by a corrective factor of 0.5 to obtain correct post-mortem times.…”
Section: Discussionmentioning
confidence: 99%
“…(Henssge, 1988) There are other organs which are used to determine body temperature. These include the brain, where a highly precise measurement is obtained in the fi rst 6 h after death [28,29]. A signifi cant factor in the case of the brain is that the weight of the body has no effect on its temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Bezfiglich der Einzelheiten wird auf die Literatur verwiesen (Henl3ge 1979(Henl3ge , 1981(Henl3ge , 1982HenBge et al 1984a, b Es empfiehlt sich, die evtl. Prfifung jener Kriterien, welche bis zur Erkennbarkeit des Ergebnisses Zeit ben6tigen, zum Zeitpunkt der Prtifung der anderen Kriterien einzuleiten (Brechen der Starre, ggf.…”
Section: Anwendung Der Teilmethode Calorunclassified